WORKERS AS GEOGRAPHICAL ACTORS - Herod, Andrew (PEGADA - A Revista da Geografia do Trabalho, 2017)
In this paper I first detail some of the geographical concepts that help us make sense of capitalism’s spatiality. I then provide several brief vignettes which illustrate how conflicts over how capitalism’s geography is made can be central to disputes both between and within groups of workers and capitalists. The paper’s purpose is to argue that understanding how social life is geographically structured can add important insights to explaining economic and political praxis.